2018
DOI: 10.1101/456665
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An infant mouse model of influenza virus transmission demonstrates the role of virus-specific shedding, humoral immunity, and sialidase expression by colonizingStreptococcus pneumoniae

Abstract: 1 9 2 0 2 1 2 2 Word count: Abstract (368), Text (4692) 2 3 2 ABSTRACT 2 4 2 5The pandemic potential of influenza A viruses (IAV) depends on the infectivity of 2 6 the host, transmissibility of the virus, and susceptibility of the recipient. While virus traits 2 7 supporting IAV transmission have been studied in detail using ferret and guinea pig 2 8 models, there is limited understanding of host traits determining transmissibility and 2 9 susceptibility because current animal models of transmission are not su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…We investigated the cellular and humoral immune responses elicited by TIV and LAIV, focusing on respiratory mucosa, and assessed whether colonization of the nasopharynx with S. pneumoniae influences vaccine immunogenicity. In agreement with previous studies 3 pneumoniae-IAV coinfection model (46). In light of these observations, it would also be interesting to investigate to what extent symptoms and inflammation caused by wild type influenza viruses are altered by concurrent Spn colonization in humans.…”
Section: Discussionsupporting
confidence: 87%
“…We investigated the cellular and humoral immune responses elicited by TIV and LAIV, focusing on respiratory mucosa, and assessed whether colonization of the nasopharynx with S. pneumoniae influences vaccine immunogenicity. In agreement with previous studies 3 pneumoniae-IAV coinfection model (46). In light of these observations, it would also be interesting to investigate to what extent symptoms and inflammation caused by wild type influenza viruses are altered by concurrent Spn colonization in humans.…”
Section: Discussionsupporting
confidence: 87%
“…Surprisingly, we observed that coinfection with Spn decreased H1N1pdm09 replication in URT as determined by viral titration of nasal washes. This observation is similar to recent data obtained from neonatal mice colonized with Spn prior to PR8 H1N1 infection (Ortigoza et al, 2018). The difference in enhancement of Spn colonization versus reduction in viral titers indicates an asymmetrical relationship between these two pathogens.…”
Section: Discussionsupporting
confidence: 92%
“…There are numerable ways the microbiota could influence attachment and entry of IAV into host cells, IAV replication, maturation of viruses with host cells, egress and dissemination, and interaction between coinfecting viral and bacterial pathogens (Jones, Le Sage, & Lakdawala, 2020). It is already clear that changes in glycosylation of the host incurred during IAV infection influence subsequent Spn colonization, and similarly changes in glycosylation via Spn affect subsequent IAV infection (Ortigoza et al, 2018; Siegel et al, 2014). It is likely that changes in host glycosylation by Spn and other bacteria also influence entry and egress of IAV, as well as its distribution in tissues across the respiratory tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The microbiota can also directly interfere with or promote invasion by the pathogen. For example, successful influenza A virus transmission is inhibited by nasal carriage of Streptococcus pneumoniae , which cleaves host nasal sialic acid, the receptor for influenza ( Ortigoza et al., 2018 ).…”
Section: The Ordered Steps Of Pathogen Tropismmentioning
confidence: 99%